An Empirical Study of Revenue Efficiency in Nepalese Life Insurance Companies - Ghimire, Rabindra (PYC Nepal Journal of Management, 2015)
The paper examines the revenue efficiency of Nepalese life insurance companies based on their periods of operation. Secondary data have been used in order to observe the revenue efficiency of companies during five-year period from 2009 to 2013. Major indicators used in the study are Commission paid to Agents, Operating Expense, Death Claim Expense, and Total Assets as input variables and Gross Premium as output variable. The study concludes that companies having longer years of business operation have better efficiency in terms of GPAC and GPOE ratios while companies with shorter period of business operation have better efficiency in terms of GPCE and GPTA ratios. The inferential test shows that there is significant difference on revenue and GPOE ratios between shorter and longer period of operation among the life insurance companies. But the difference is not significant on GPAC ratio, GPCE and GPTA ratios in between shorter and longer period of operation among the life insurance companies.